KEDUDUKAN ANAK ANGKAT DALAM PERSPEKTIF HUKUM ISLAM, HUKUM ADAT DAN HUKUM PERDATA - Rais, Muhammad (Fakultas Syariah dan Hukum Islam Institut Agama Islam Negeri (IAIN) Parepare, 2016)
This paper aims to compare the three sistems of law on the status of adopted children by using normative juridical approach. It concluded that the position of adopted children in the sistem of Islamic law does not sever the relationship between the adopted child and his biological parents then adopted children do not become the heir of his adoptive father except through wajibah testament. The amount of inheritance is not more than 1/3. Positive law stipulates that adopted children have equal position with biological children of foster parents so that the adopted child becomes heir adoptive parents for adoption severed all civil relationship between the child and biological parents. While in traditional law, the position of adoptive children depends on the laws in force in a customs area because some areas in Indonesia is different in determining position an adopted child.